Clinical effectiveness and patient perspectives of different treatment strategies for tics in children and adolescents with Tourette syndrome: a systematic review and qualitative analysis - Hollis, Chris; Pennant, Mary; Cuenca, Jose; Glazebrook, Cris; Kendall, Tim; Whittington, Craig; Stockton, Sarah; Larsson, Linnéa; Bunton, Penny; Dobson, Suzanne; Groom, Madeleine J.; Hedderly, Tammy; et al. (NIHR Health Technology Assessment Programme, 2016)
Background: Tourette syndrome (TS) is a neurodevelopmental condition characterised by chronic motor and vocal tics affecting up to 1% of school-age children and young people and is associated with significant distress and psychosocial impairment. Objective: To conduct a systematic review of the benefits and risks of pharmacological, behavioural and physical interventions for tics in children and young people with TS (part 1) and to explore the experience of treatment and services from the perspective of young people with TS and their parents (part 2).